Acupuncture and nutritional parallels in obesity: a narrative review of multi-pathway modulation of the microbiota–gut–brain axis - Ma, Kun; Wang, Feifei; Zhang, Xinying; Guo, Liangqing; Huang, Yanqin (Frontiers in Nutrition, 2025)
Obesity is a complex metabolic disorder that is intricately linked to dysregulation of the microbiota–gut–brain axis (MGBA), a key pathway also targeted by nutritional interventions. Acupuncture, as a non-pharmacological and integrative approach, has shown promising effects in weight control and metabolic improvement, yet its underlying mechanisms remain to be systematically clarified from a nutritional and metabolic perspective. This review outlines an integrative framework by which acupuncture modulates obesity through the MGBA, emphasizing shared targets with diet-based interventions such as short-chain fatty acids (SCFAs), glucagon-like peptide-1 (GLP-1), and G protein-coupled receptors (e.g., GPR43). We discuss how acupuncture improves microbial diversity, enhances gut barrier integrity, and regulates nutrient-derived signaling molecules, thereby influencing energy metabolism, appetite control, and inflammatory responses. Furthermore, we explore the convergence of neural, endocrine, and immune networks within the MGBA, positioning acupuncture as a systemic metabolic modulator analogous to nutritional therapeutics. This conceptual model provides novel insights into multi-targeted interventions for obesity, suggesting that acupuncture may serve as a complementary strategy to nutritional modulation in restoring metabolic homeostasis.